HSF1: Essential for Myeloma Cell Survival and A Promising Therapeutic Target - Fok, Jacqueline H L (Clin Cancer Res, 2018)
PURPOSE: Myeloma is a plasma cell malignancy characterized by the overproduction of immunoglobulin and is therefore susceptible to therapies targeting protein homeostasis. We hypothesized that heat shock factor 1 (HSF1) was an attractive therapeutic target for myeloma due to its direct regulation of transcriptional programs implicated in both protein homeostasis and the oncogenic phenotype. Here, we interrogate HSF1 as a therapeutic target in myeloma using bioinformatic, genetic and pharmacological means. EXPERIMENTAL DESIGN AND RESULTS: To assess the clinical relevance of this novel target, we analyzed publicly available gene expression datasets and found that expression of HSF1 and its target genes were associated with poorer myeloma patient survival. Sh-RNA-mediated knockdown or pharmacological inhibition of the HSF1 pathway with a novel chemical probe, CCT251236, or with KRIBB11, led to caspase-mediated cell death that was associated with an increase in EIF2α phosphorylation, CHOP expression and a decrease in overall protein synthesis. Importantly, both CCT251236 and KRIBB11 induced cytotoxicity in human myeloma cell lines and patient-derived primary myeloma cells with a therapeutic window over normal cells. Pharmacological inhibition induced tumor growth inhibition and was well-tolerated in a human myeloma xenograft murine model with evidence of pharmacodynamic biomarker modulation. CONCLUSION: Taken together, our studies demonstrate the dependence of myeloma cells on HSF1 for survival and support the clinical evaluation of pharmacological inhibitors of the HSF1 pathway in myeloma.